22. THE LATERAL ANTEBRACHIAL NEUROFASCIOCUTANEOUS FLAP WITH DETECTING THE LOCATION OF THE DISTAL PERFORATORS OF THE RADIAL ARTERY FOR HAND SOFT TISSUE DEFECTS RECONSTRUCTION (Vietnam Journal of Community Medicine, 2024)
Background and objectives: There is still no consensus among researchers regarding the pivot point of the distally based lateral antebrachial neurofasciocutaneous flap, using for coverage of hand soft tissue defects. Therefore, this study aimed to determine the approriate location of the distal perforators of the radial artery as the pivot point of the lateral antebrachial neurofasciocutaneous flap. Materials and Methods: The prospective case series study applies the lateral antebrachial neurofasciocutaneous flap with detecting the location of the distal perforators of the radial artery for reconstruction of hand soft tissue defects with exposed tendon or bone. All cases were followed up at least 6 months. Results: Thirty-three flaps (33/35) were survived (94,3%). Two flaps (02/35) suffered from distal superficial necrosis. The pivot point was located above the radial styloid process: 4 cm (26 flaps), 6 cm (9 flaps). The flap can cover many sides of hand, without complication and sequel. Dicussion: Detecting the location of the distal perforators of the radial artery is the important step in harvesting the lateral antebrachial neurofasciocutaneous flap for reconstruction of hand soft tissue defects. Conclusions: The distally based lateral antebrachial neurofasciocutaneous flap with detecting the location of the distal perforators of the radial artery is useful for coverage of hand soft tissue defects, without complication and sequel.
Keywords: The distally based lateral antebrachial neurofasciocutaneous flap.